ILRI programme: Progress, achievements and impact 1994-1998. Proceedings of a workshop - Hanson, Jean (International Livestock Centre for Africa, 1994)
Lack of seeds has been identified as an important limitation to increase food production by CGIAR. ILCA and ICARDA have established seed units to address this constraint and promote the supply of seeds of their mandate crops. Much of the seed used for sowing crops in developing countries is produced in the informal sector by farmers. This is especially important for minor crops where there is no organised commercial activity. The major producer at this level is the smallholder farmer, who is considered to be resource poor, working relatively small land holdings and with most of the labour being supplied by the household. Recognising the importance of this informal seed production by farmers, this workshop was conducted to assess the knowledge base on seed production by smallholders, to identify constraints to increasing seed production, to identify areas where further research is required to support smallholder seed production and to make recommendations.